African-American Women’s Perceptions and Experiences About Breastfeeding - Obeng, Cecilia S.; Emetu, Roberta E.; Curtis, Terry J. (Frontiers in Public Health, 2015)
There are health benefits to breastfeeding for both mothers and their children. The preventive health effects of breastfeeding continue into adulthood, lowering rate of various chronic illnesses. African-American women, especially of lower socioeconomic status, are less likely to breastfeed in comparison to their racial and ethnic counterparts. The purpose of this study is to explore how African-American women experience breastfeeding in the early stages of postpartum care. Two focus groups (N = 20, 10 in each group) were conducted with African-American mothers. Results revealed that participants felt that there were health benefits to breastfeeding, and organizations such as Women, Infants, and Children (WIC) provided support. However, participants stated that lack of information, negative perceptions, and unforeseen circumstances were barriers to breastfeeding. This study proposes support and interventions for this group to increase breastfeeding among this population.